2021
DOI: 10.33258/birci.v4i2.1996
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Work Discipline, Work Ethos and Work Environment on Employee Work Achievement: Lessons from Local Organization in an Emerging Country

Abstract: The Office of Industry, Trade, Cooperatives and Small and Medium Enterprises of Yapen Islands Regency, Papua, as a local government agency is obliged to foster, protect, and pay attention to issues related to industry, trade, cooperatives, and small and medium enterprises. Good employee performance is important in order to support the smooth running of official duties. This study aims to examine and analyze the effect of work discipline, work ethic and work environment on employee work performance at the Depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
2
4
0
1
Order By: Relevance
“…This research is in line with the results of research by Sipahelut et al (2021), which shows a relationship between work discipline and work productivity. With discipline, it is hoped that the work will be more effective.…”
Section: B Effect Of Work Discipline On Nurse Work Productivitysupporting
confidence: 91%
“…This research is in line with the results of research by Sipahelut et al (2021), which shows a relationship between work discipline and work productivity. With discipline, it is hoped that the work will be more effective.…”
Section: B Effect Of Work Discipline On Nurse Work Productivitysupporting
confidence: 91%
“…Departing from these indicators, increasing work discipline can also affect employee performance. Proven research from Gotama and Rusdiana (2022) concluded that work discipline affects employee performance positively and significantly, which is in line with research from (Sipahelut et al, 2021 andSutoro, 2018).…”
Section: Work Discipline Has a Significant Positive Effect On Employe...supporting
confidence: 66%
“…It is known that as many as 25 works of literature show that work discipline affects the dependent variable in each of these studies. Of these, no literature uses a single variable, meaning that 25 of the literature uses more than one variable, and variables that are partners in work disciplines such as the work environment in research (Prasetyo et al 2021, Sipahelut et al 2021, leadership in research (Permana et al 2019, Rivai 2017, Akbaruddin & Bayu 2019, work motivation in research (Suci 2020, Alhempi, et al 2021, Dewi, et al 2018, Eka 2018), and others.…”
Section: Work Discipline Has a Positive And Significant Effect On Per...mentioning
confidence: 99%
“…Consciousness is a person who follows all the rules and understands his responsibility. Willingness is a person's attitude, behavior, and actions in accordance with regulations, whether written or not (Alfian & Afrial, 2020;Cahya et al, 2021;Hustia, 2020;Sipahelut et al, 2021). Meanwhile, Kusumasari, (2022) work discipline is a mental attitude that is reflected in the level of action or behavior in the form of obedience and adherence to the rules and regulations set either by the government or the ethics, norms and rules that apply in the environment or organization.…”
Section: Work Disciplinementioning
confidence: 99%
“…This shows the importance of having a strong sense of discipline in organizations in general. Work discipline is something that must always be considered (Alfian & Afrial, 2020;Hustia, 2020;Sipahelut et al, 2021). The Team's safety depends on its ability to understand applicable laws.…”
Section: Introductionmentioning
confidence: 99%